1998
DOI: 10.1172/jci949
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils exposed to bacterial lipopolysaccharide upregulate NADPH oxidase assembly.

Abstract: Bacterial LPS is a pluripotent agonist for PMNs. Although it does not activate the NADPH-dependent oxidase directly, LPS renders PMNs more responsive to other stimuli, a phenomenon known as "priming." Since the mechanism of LPS-dependent priming is incompletely understood, we investigated its effects on assembly and activation of the NADPH oxidase. LPS pretreatment increased superoxide (O2-) generation nearly 10-fold in response to N-formyl methionyl leucyl phenylalanine (fMLP). In a broken-cell O2--generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
235
0
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(252 citation statements)
references
References 51 publications
10
235
0
7
Order By: Relevance
“…Endotoxin not only is a priming agent 6 but has been reported to fully activate neutrophils 12,13 by up-regulating the NADPH oxidase assembly. 32 The highest levels of endotoxin reported in patients with liver disease are found in portal venous blood, 33,34 highlighting the importance of the bowel and altered gut permeability as a possible source of endotoxin. 35 However, the difficulties with the measurement of endotoxin are reflected in the wide range of values in the literature and make this an unreliable indicator on which to base further management.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin not only is a priming agent 6 but has been reported to fully activate neutrophils 12,13 by up-regulating the NADPH oxidase assembly. 32 The highest levels of endotoxin reported in patients with liver disease are found in portal venous blood, 33,34 highlighting the importance of the bowel and altered gut permeability as a possible source of endotoxin. 35 However, the difficulties with the measurement of endotoxin are reflected in the wide range of values in the literature and make this an unreliable indicator on which to base further management.…”
Section: Discussionmentioning
confidence: 99%
“…The NADPH oxidase assembles on flavocytochrome b 558 , which is expressed at low levels in the plasma membrane of resting cells. DeLeo and colleagues (3) reported that exposure of PMNs to LPS leads to an increase in the amount of flavocytochrome b 558 expressed in the plasma membrane from 25% to about 40% of total cellular content, suggesting that redistribution of this NADPH oxidase component is one mechanism by which the respiratory burst is primed. The results of the present study extend the observations of DeLeo et al (3) to a second priming agent, TNF␣, and provide further evidence that translocation of flavocytochrome b 558 to the plasma membrane is one mechanism by which PMN priming occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In resting cells 10 -25% of flavocytochrome b 558 is located in the plasma membrane, with the remaining 75-90% distributed among secretory vesicles and gelatinase and specific granules (2,3).…”
Section: And Gp91mentioning
confidence: 99%
See 1 more Smart Citation
“…Moore, Silliman, and others (52)(53)(54) have shown that PAF is a primary agent responsible for neutrophil priming in human trauma victims. In contrast, LPS and TNF␣ are the likely priming agents in acute pancreatitis (55,56), as well as in many patients with sepsis (57)(58)(59)(60)(61), and these agents have been directly implicated in causing acute lung injury (62)(63)(64)(65) and ischemia-induced acute renal failure (66).…”
mentioning
confidence: 99%